Pengaruh Kompensasi dan Lingkungan Kerja terhadap Produktivitas Kerja Karyawan: (Studi Pada Rumah Sakit Dian Husada Mojokerto) - Siswandari, Nabillah; Baidlowi, Imam; Hadi Poernomo, Agoes (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
One of the important factors that can influence employee work productivity in an agency or company is compensation and the work environment. Appropriate and appropriate compensation as well as a comfortable and very supportive work environment can increase employee work productivity. In this research, the aim of the research was to determine the effect of Compensation and work environment on employee work productivity at Dian Husada Hospital, Mojokerto. The type of research used is an associative quantitative method with data collection techniques used are interviews and distributing questionnaires to employees. The population in this study were core employees at Dian Husada Hospital, Mojokerto. The research sample used was 50 people using a saturated sampling technique. The results of this research show that compensation and environmental variables have a partially positive and significant effect on employee work productivity. And simultaneously compensation and the work environment have a positive and significant effect on employee work productivity at Dian Husada Hospital, Mojokerto.